2020
DOI: 10.1021/acs.energyfuels.0c02486
|View full text |Cite
|
Sign up to set email alerts
|

Study of Rheological Properties and Micro-mechanism of Heavy Oil Emulsion Prepared via Ultrasonic Dispersion

Abstract: An emulsion is a dispersion with a complex mechanism of formation and a poor stability. In the preparation of emulsions, the used surfactant concentration, oil−water ratio, and kinetic conditions affect the type, microscopic characteristics, and rheological properties of the emulsions. As a result of its high viscosity, it is difficult to disperse the heavy oil with mechanical agitation, and the stability of the emulsion system formed is poor; hence, it is challenging to study its rheological properties. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In the case of the bitumen-aqueous interface, optimal primary recovery efficiency was found to be associated with a maximum in interfacial electric charge and a minimum in interfacial tension [39]. However, Jamin's effect still occur when emulsified O/W droplets flow through small throats of porous media [40]. Furthermore, the pollution problems and the cost resulted by alkali's serious adsorption or caused by the produced water process and a large amount of the chemical agents injected inspired us to put forward a more environmentally scheme.…”
Section: Introductionmentioning
confidence: 97%
“…In the case of the bitumen-aqueous interface, optimal primary recovery efficiency was found to be associated with a maximum in interfacial electric charge and a minimum in interfacial tension [39]. However, Jamin's effect still occur when emulsified O/W droplets flow through small throats of porous media [40]. Furthermore, the pollution problems and the cost resulted by alkali's serious adsorption or caused by the produced water process and a large amount of the chemical agents injected inspired us to put forward a more environmentally scheme.…”
Section: Introductionmentioning
confidence: 97%
“…The emulsification flooding agent would act with the rock surface and make it gradually become water wet so that crude oil would easily peel off from the rock surface to form the O/W emulsion. Jamin effect would occur when emulsified oil droplets flow through small throats of porous media. The swept area would increase for the temporary plugging effect of the oil droplet. Soo et al found that the retention and trapping effects of oil droplets can lead to droplet fluidity decrease in porous media . Therefore, Arhuma et al proposed to use the apparent viscosity of O/W emulsions when flowing in porous media to characterize its fluidity .…”
Section: Introductionmentioning
confidence: 99%
“…The development of gas fields is often accompanied by the production of condensate oil [1][2][3]. It is highly challenging to separate the condensate oil from the emulsion [4,5]. During the production process, a significant amount of surfactant liquid is injected into the gas well [6,7].…”
Section: Introductionmentioning
confidence: 99%